THE EFFECT OF TRUST AND RISK PERCEPTION ON PURCHASE DECISIONS USING THE SHOPEE PAYLATER METHOD IN DOLOK MERAWAN VILLAGE - Rumiris Siahaan; Rachmawati Purba; Abednego Ketaren (CV. Radja Publika, 2025)
This study aims to analyze the influence of trust and perceived risk on purchase decisions in the use of Shopee PayLater payment method (a case study on Shopee PayLater users in Dolok Merawan District). This research employed a quantitative approach with a survey technique, and data were collected using questionnaires distributed to 96 respondents. Data analysis was conducted through validity and reliability tests, multiple linear regression, as well as t-test and F-test using SPSS version 25.00 software. The results show that trust has a significant effect on purchase decisions, while perceived risk does not have a significant effect. These findings indicate that trust is a factor influencing purchase decisions, while perceived risk does not significantly affect the use of Shopee PayLater